TINJAUAN KRIMINOLOGI TERHADAP PELAKU KEKERASAN DALAM RUMAH TANGGA YANG TERJADI DI KABUPATEN LANDAK - NIM. A1012181056, JUNIAR CHENDY EVARAS (Fakultas Hukum Universitas Tanjungpura, 2025)
ABSTRACTThere were 3 cases of domestic violence that occurred in Landak Regency, carried out by husbands against wives. The first domestic violence in Amboyo village, Ngabang District, Landak Regency was on September 7 2021 at 12.00 WIB, which was caused by the husband being annoyed by his wife's words and the wife's actions of throwing bags and trash cans which then caused an argument. However, the wife's anger started because the husband had another wife and sold the shop house.The peak was that the husband punched the victim in the face which then caused the victim's activities to be disrupted due to bruises on the left side of his face close to his eyes so that his vision was slightly impaired. The second domestic violence in Amang village, Ngabang District, Landak Regency on April 30 2023 at 18.00 WIB was caused by the wife being upset that her husband had not paid off the debt at the shop which then led to an argument. The wife, who continued to be angry, caused the husband to kick the wife's head, causing the victim's body to be pushed forward and her face to hit the cooking area. As a result, the victim suffered injuries to his face, specifically on the bridge of his nose, bleeding and bruising on his hands due to hot water spilling on the cauldron.The third domestic violence in Kedama village, Kuala Behe District, Landak Regency on 9 and 10 November 2021 at 20.00 WIB was caused by the husband being annoyed or embarrassed where the wife told the perpetrator that she married the perpetrator because she ran away. This happened after 3 months after the marriage in 2012 and the perpetrator then kept it hidden for years. And the culmination of the incident was because he was upset when he found out that the victim witness/wife was having an affair with someone theperpetrator did not know and the victim also said that the perpetrator could not satisfy his lust, which made the perpetrator emotional and committed violence or abused the victim. Keywords: Criminology, Doer, Violence, Domestic. ABSTRAKKekerasan dalam rumah tangga Yang terjadi di Kabupaten Landak sebanyak 3 kasus dilakukan oleh suami terhadap istri. KDRT pertama di desa Amboyo Kecamatan Ngabang Kabupaten Landak pada tangal 7 September 2021 pada pukul 12.00 WIB yang disebabkan suami kesal dengan perkataan istri serta tindakan istri yang melemparkan tas serta tempat sampah yang kemudian menyebabkan pertengkaran. Akan tetapi istri marah berawal karena suami telah memiliki istri lain dan menjual ruko. Puncaknya suami meninju korban ke wajah yang kemudian menyebabkan aktivitas korban menjadi terganggu karena luka memar di wajah sebelah kiri dekat dengan mata sehingga penglihatan sedikit terganggu. KDRT kedua di desa Amang Kecamatan Ngabang Kabupaten Landak pada tanggal 30 April 2023 pada pukul 18.00 WIB yang disebabkan istri kesal suami belum melunasi hutang di warung yang kemudian menyebabkan pertengkaran. Istri yang terus marah menyebabkan suami menendang kepala istri mengakibatkan badan korban terdorong ke arah depan dan wajah membentur tempat memasak. Akibatnya korban mengalami luka di bagian wajah tepatnya di bagian batang hidung dan mengeluarkan darah serta memar pada bagian tangan akibat terkena tumpahan air panas pada kuali.KDRT ketiga di desa Kedama Kecamatan Kuala Behe Kabupaten Landak pada tangal 9 dan 10 November 2021 pada pukul 20.00 WIB yang disebabkan suami kesal atau malu dimana istri bercerita kepada pelaku bahwa menikah dengan pelaku dikarenakan pelarian, hal ini terjadi setelah 3 bulan setelah nikah di tahun 2012 dan hal itu kemudian dipendam oleh pelaku selama bertahun-tahun. Serta puncaknya kejadian tersebut dikarenakan kesal mengetahui saksi korban/istri selingkuh dengan orang yang tidak pelaku kenal dan korban juga pernah berkata bahwa pelaku tidak dapat memuaskan nafsunya yang membuat pelaku emosi dan melakukan kekerasan atau menganiaya korban..Kata Kunci: Kriminologi, Pelaku, Kekerasan, Rumah Tangga